Pengaruh Penggunaan Media FlipBook Digital terhadap Keterampilan Menulis Siswa Sekolah Dasar - Masruro, Nadia Aurelita; Amelia, Chairunnisa (Universitas Muhammadiyah Magelang, 2026)
The study has three objectives which include: (1) assessing students’ basic narrative writing abilities before they use digital flipbook media; (2) evaluating students complete narrative writing abilties after they use digital flipbook media; and (3) studying how digital flipbook media affects the narrative writing development of fourth-grade students at the ‘Aisyiyah Guidance Center in Kampung Pandan Malaysia. The study uses a quantitative approach with a pre-experimental design of the one group pretest-posttest type. The research subjects consisted 6 students. Data collection was conducted through narrative writing tesis before and after the implementation of digital flipbook media. The data were analyzed using the Shapiro-Wilk normalty test and paired sample t test. The analysis results shoved a significant improvement in students’ narrative writing skills after using digital flipbook media, with a significance value of 0,000 < 0,05. These findings indicate that digital flipbook media is effective in improving elementary school students’ NARRATIVE Writing skills through the presentation of interactive engaging material that motivates student in the process of learning Indonesian